2004
DOI: 10.1159/000077359
|View full text |Cite
|
Sign up to set email alerts
|

Role of Substance P in an NC/Nga Mouse Model of Atopic Dermatitis-Like Disease

Abstract: Background: Atopic dermatitis (AD) can be exacerbated or induced in genetically predisposed individuals by psychological stress, which causes the release of substance P (SP). Therefore, SP may play an etiological role in the mechanisms underlying AD. Methods: Changes in the number of mast cells and SP-containing mast cells in lesional skin, and the serum concentrations of SP and IgE during the development of AD-like disease up to 8 weeks after the start of picryl chloride (PiCl) induction in NC/Nga mice were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 28 publications
7
47
1
1
Order By: Relevance
“…[24][25][26] In accordance with this previous finding, the clinical skin severity in control group increased gradually depending on the times of challenge with PiCl and reached a maximum on the 63rd day after the sensitization. All of the mice in control group exhibited AD-like skin lesions including eczema, erythema, excoriation and hemorrhage in the face, dryness, scaling and alopecia in the neck and dorsal skin ( Fig.…”
Section: Comparison Of Skin Severitysupporting
confidence: 81%
See 2 more Smart Citations
“…[24][25][26] In accordance with this previous finding, the clinical skin severity in control group increased gradually depending on the times of challenge with PiCl and reached a maximum on the 63rd day after the sensitization. All of the mice in control group exhibited AD-like skin lesions including eczema, erythema, excoriation and hemorrhage in the face, dryness, scaling and alopecia in the neck and dorsal skin ( Fig.…”
Section: Comparison Of Skin Severitysupporting
confidence: 81%
“…The total scores of the skin severity are defined as the sum of the individual score grades from score 0 (no symptoms), score 1 (mild), score 2 (moderate), and score 3 (severe) for each of the following 4 signs and symptoms, erythema (hemorrhage), edema, excoriation (erosion), and dryness (scaling). [25][26][27] Histological Study Mice were sacrificed on the 63rd day after sensitization. The auricular skin was removed, fixed in 10% formalin, embedded into paraffin, cut in 10-mm sections, stained with hematoxylin-eosin solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mediators, such as substance P, are believed to play important roles in the symptoms observed in NC / Nga mice and humans. Substance P is reported to play an important role in the pathogenesis of human atopic dermatitis (16,40,41), and some authors have suggested using in vivo models (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha observado que la sustancia P (neuropéptido) se encuentra involucrado en la activación y regulación de la respuesta inmune innata y la adaptativa y sus niveles están aumentados en piel y en sangre de los pacientes que padecen DA, así como alteraciones en las células dendríticas (células presentadoras de antígeno: APC) especialmente las células de Langerhans y las células dendríticas epidér-micas inflamatorias (6,23,24).…”
Section: Fisiopatologíaunclassified